The Role of Different Planting Types in Mitigating Urban Heat Island Effects: A Case Study of Gaziantep, Turkey - Ahmet Salih Günaydın; Murat Yücekaya (Journal of Agricultural Sciences)
The growth of cities and increase in their structural density lead to several problems. The most important of these is the formation of urban heat islands and the decrease in the bioclimatic comfort levels. This study focuses on the effect of different planting alternatives on bioclimatic comfort. In this context, different planting options with only leafy, only coniferous, leafy and coniferous at half at 4 m, 6 m, and 8 m intervals along with the current planting state of the study area in Gaziantep, Turkey were prepared. These plans were simulated with ENVI-met software. As a result of the study, coniferous plants were observed to have a cooling effect of approximately 2 °C – 2.5 °C compared to the leafy ones. In the simulation results of the map obtained with coniferous mixed plants, it was determined that the cooling effect values of only coniferous and only leafy plants were at almost average. Relative humidity was 15% higher in the plan conducted with coniferous plants compared to leafy plants. It was about 8% higher than leafy ones in mixed planning. There was no significant change in wind speed maps. In the plans with 4 m intervals on average radiation temperature maps, the refreshing effect of the coniferous was more than the leafy. As a result of the study, it was found out that the highest cooling effect was achieved in the planting plan created at 4 m intervals using coniferous plants.